Macaca fascicularis and Macaca nemestrina infected with zoonotic malaria parasites are widely distributed in Sarawak, Malaysian Borneo - Thamayanthi, Nada-Raja; Khamisah, Abdul Kadir; Paul Cliff Simon, Divis; Dayang S.A., Mohamad; Asmad, Matusop; Balbir Singh, Mohan Singh (Nature, 2022)
Human infections with Plasmodium knowlesi, a malaria parasite of Macaca fascicularis and Macaca nemestrina (long-tailed and pig-tailed macaques respectively), occur throughout Southeast Asia, especially Malaysian Borneo. Other naturally-acquired human infections with malaria parasites from macaques in Southeast Asia are P. cynomolgi, P. inui-like, P. coatneyi and P. simiovale. In Sarawak, Malaysian Borneo, M. fascicularis and M. nemestrina from only the Kapit Division have been examined previously for malaria parasites. In order to determine the distribution of P. knowlesi and other zoonotic malaria parasites, 73 macaque blood samples derived from 7 other administrative divisions in Sarawak were studied. Of 45 blood samples from M. fascicularis and 28 from M. nemestrina tested by nested PCR assays, 23 (51.1%) M. fascicularis and 15 (53.6%) M. nemestrina samples were positive for Plasmodium DNA. Thirty-two of these macaques from 7 divisions sampled, harboured either single (n = 12), double (n = 9), triple (n = 7) or quadruple (n = 4) infections of P. knowlesi, P. inui, P. cynomolgi and P. coatneyi, while the infecting species of Plasmodium could not be identified for 6 samples. P. knowlesi was detected in 15.5% (7/45) M. fascicularis and in 7.1% (2/28) M. nemestrina sampled. Despite the small number of samples analysed from each administrative division, the current study indicates that macaques infected with the zoonotic malaria parasites P. knowlesi, P. cynomolgi, P. inui and P. coatneyi are widely distributed throughout Sarawak, Malaysian Borneo. Travelers to forested areas in Sarawak should be made aware of the potential risk of acquiring zoonotic malaria.